Tips for Success in Facing Accreditation - A. Zebar; Muammar Rinaldi; Novi Cynthia Yusnita (Outline Journal of Community Development, 2024)
Nana Nini Education Center is a course and education institution founded on September 16 2002 which provides English language teaching and education to the community in Labuhanbatu. After 20 years they are trying to establish a new foundation, namely on March 17 2022 because they want to expand into the world of PAUD and Elementary Schools. In choosing an educational institution, most parents will of course choose a school with excellent qualifications. Therefore, it is necessary to accredit school institutions so that the quality of these institutions is superior and the best.